LIBERAL DEMOCRACY: THEORETICAL APPROACHES, INSTITUTIONS, RESILIENCE AND ASSESSMENT OF DEMOCRACY - Revenko, Denis (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2025)
The article examines the crisis manifestations of liberal democratic institutions in Eastern European countries. It reveals the specifics of their functioning under conditions of political turbulence, characterized by the rise of populism, increasing political polarization, external pressure from authoritarian regimes, and internal dysfunctions of governance. The key institutional mechanisms for maintaining democratic order are analyzed, and their vulnerability to crisis factors is identified.The study characterizes theoretical approaches to understanding the resilience of democracy, in particular the concept of «militant democracy», which envisages the application of temporary restrictions in order to protect democratic regimes from anti-democratic actors. It is shown that such measures, on the one hand, may strengthen institutional resilience, while on the other, they create risks of prolonging restrictions and gradual erosion of liberal values. Special attention is paid to the analysis of Ukraine’s institutional dynamics after 2014 and under the conditions of martial law. The practice of banning pro-Russian political parties, conducting decommunization measures, and applying other instruments of «self-defense» of democracy is highlighted. At the same time, the asymmetry of these processes and ongoing debates regardingtheir  conformity with liberal democratic principles are emphasized.The article also considers   democracy indices (Freedom House, V-Dem, Economist Intelligence Unit) as tools for assessing the state of democracy. It demonstrates that temporary restrictions introduced during crisis periods reduce scores in the components of «civil liberties» and «liberal institutions», but do not always indicate long-term democratic backsliding. It is concluded that the development of liberal democracy in Eastern European countries is determined by the ability of institutions to maintain a balance between necessary restrictions in times of crisis and the preservation of fundamental democratic principles in the long-term perspective. Moreover, the findings underline the importance of civic engagement, international support, and ongoing reforms as essential factors for strengthening democratic resilience. Ultimately, the study suggests that the future trajectory of liberal democracy in the region will depend on how successfully societies adapt to challenges without sacrificing their core values.